Controlling Retail Development between Restrictiveness and Innovation: insights from Portugal - Guimarães, Pedro Porfírio (2018)
Retail planning policies have become more important in the course of retail change that negatively affected traditional trade centers of several Western European countries after the 1950s. Consequently, governments have begun to more actively control the development and location of new large-scale retail developments. The objective of this article is to analyze the evolution of the policy designed to control the implementation of new retail developments in Portugal. We aim to answer the following research question: “What have been the main characteristics of planning permissions for new retail developments in Portugal?” Besides the theoretical support, our research was based on the analysis of the Portuguese legislation implemented to regulate retail, especially major retail developments. We conclude that, overall, retail planning policies balance between periods characterized by the restrictiveness regarding the opening of new large retail developments and periods where the legislation is smoother, mainly with the objective of increasing innovation in retail, through new formats and companies. Consequently, although ambiguous, this control of retail development has allowed the government to respond both to private promoters and independent retailers.